Institutional change and legitimacy via urban elections? People's awareness of elections and participation in urban neighbourhoods (shequ) - Heberer, Thomas (2006)
Abstract: "This paper analyses institutional reforms and political participation, most notably indirect and direct elections of residential committees (RC), in China's urban neighbourhoods and communities (shequ). It shows that these elections at present are not meaningful to the majority of city dwellers as the RCs have little decision-making power and no revenues generated by a collective economy as in most of China's villages. RCs are primarily important to those weaker strata of society who depend on the state to be provided with social services and financial support - tasks that the RCs are forced to assume on behalf of higher government authorities. Nevertheless, the author finds that as limited the significance of - and knowledge about - RC elections in the daily lives of China's urban dwellers still are, they still have some influence on political awareness and participation. For instance, they make people voice more opinions in their shequ, which may be a good starting point for mor